What constitutes student–university brand relationship? Malaysian students’ perspective - Sharizal, Hashim; Norjaya, Mohd Yasin; Siti Aisyah, Ya’kob (Taylor and Francis Ltd., 2020)
The concept of customer-brand relationship (CBR) is becoming increasingly important. However, the description of what constitutes student–university brand relationship is relatively limited. Underpinned by social exchange theory, this study proposes student–university brand relationship formation that comprises of utility (UV), hedonic (HV) and relational values (RV) as the antecedents, brand relationship quality (BRQ), as the mediator, and brand resonance (BR) as the consequence of CBR. With a set of usable data from 701 samples of Malaysian postgraduate students, the structural equation modelling (PLS) was utilized. The results reveal the mediating effect of BRQ in the relationships between customer values (UV, HV and RV) and BR. Therefore, considering student’s psychological ties as the focus in brand relationship strategy can help the university to understand how to create a greater bonding and favourable university’s brand relationship response.